2021
DOI: 10.1007/s00384-021-03969-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for upper and lower type prolonged postoperative ileus following surgery for Crohn’s disease

Abstract: Purpose Prolonged postoperative ileus (PPOI) is common after bowel resections, especially in Crohn’s disease (CD). The pathophysiology of PPOI is not fully understood. PPOI could affect only the upper or lower gastrointestinal (GI) tract. The aim of this study was to assess risk factors for diverse types of PPOI, particularly to differentiate PPOI of upper and lower GI tract. Methods A retrospective analysis of 163 patients with CD undergoing ileocecal res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…It must be highlighted that the current study did not intend to identify such a link, and nearly a third of the patients did not have baseline FC measurements. Also, young age at diagnosis, disease location, and smoking were not found to be risk factors in the cases that were analyzed, even though other studies reported them as such (2,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 76%
“…It must be highlighted that the current study did not intend to identify such a link, and nearly a third of the patients did not have baseline FC measurements. Also, young age at diagnosis, disease location, and smoking were not found to be risk factors in the cases that were analyzed, even though other studies reported them as such (2,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 76%
“…The average period from surgery to bowel movement also depends upon the age, indication and duration of surgery performed, presence of Ryle's tube, period to initiation of mobilization, presence of abdominal drains and intraoperative bowel condition. The edematous bowel may have increased postoperative ileus [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seven retrospective studies analyzed incidence and risk factors for post-operative complications in CD patients undergoing bowel resection, showing that pre-operative anemia was associated with a higher risk of post-operative morbidity and mortality [172][173][174], higher risk of sepsis [160], surgical site infection [175] and post-surgical complications [176] such as prolonged postoperative ileus [177].…”
Section: Post-operative Recurrence and Surgery-related Complicationsmentioning
confidence: 99%